Impact of Mesoscale Motions on Monin-Obukhov Similarity and Surface Energy Balance over a Homogeneous Surface - Yang Guo; Hongchao Zuo (Advances in Meteorology)
Mesoscale motions are an important factor influencing the applicability of Monin-Obukhov similar theory (MOST) and the surface energy balance. The heterogeneous surface and the vegetation-covered surface also increase the complexity of these two problems. In order to understand the effect of mesoscale motions on turbulent fluxes more clearly, this study analyzes the impact of mesoscale motions on MOST and surface energy balance using the multiresolution decomposition method and the observational data over a homogeneous bare soil surface. Two conclusions are obtained: (1) When mesoscale motions are excluded, the scatter of similarity relations is evidently reduced; the observed values of the dimensionless velocity gradient and dimensionless temperature gradient in stable conditions become less than the values estimated using the universal functions, and the flux-variance relationship for temperature clearly deviates from the −1/3 power law. (2) When mesoscale motions are excluded, the number of energy balance closure outliers at night is dramatically reduced, and the energy balance ratio (EBR) is increased. However, when turbulent mixing is weak, even if mesoscale motions are excluded, the EBR is still relatively low, which is possibly due to the fact that the energy is mainly transported by mesoscale motions instead of turbulence.